Analisis Metode Pembelajaran Bahasa Arab Pada Madrasah Tsanawiyah Al-Amiriyah Pondok Pesantren Darussalam Blokagung Kabupaten Banyuwangi - M. Alaika Nasrullah (IAI Darussalam, 2017)
This study aims to describe the methods used and obstacles faced by Arabic teachers at Al-Amiriyah High School, Pondok Pesantren Darussalam, Blokagung, Banyuwangi. Qualitative research methods and descriptive analysis are applied together with data collection techniques through interviews and documentary archive investigations on student profiles, Arabic language teachers, and other school support systems. The research has yielded some findings such as that in teaching Arabic teachers apply several methods of reading (qira'ah), translation (tarjamah), memorizing (Hafdz), composition (insya'), and dictation (imla'). These five methods of teaching Arabic have been practiced well in school